Neutron capture reactions for nuclear astrophysics: Development & characterization of an innovative detection setup based on trans-Stilbene organic scintillators - Papanikolaou, Dimitris; Musumarra, Agatino; Pellegriti, Maria Grazie; Patronis, Nikolaos (HNPS Advances in Nuclear Physics, 2025)
Neutron capture reactions are essential for understanding stellar nucleosynthesis beyond iron and the formation of elements in the universe. This study presents the development and characterization of a novel detection setup utilizing trans-Stilbene organic scintillators, developed at DFA (Dipartimento di Fisica e Astronomia "Ettore Majorana", Catania) and INFN-CT, to enhance neutron capture measurements for nuclear astrophysics. A fully symmetrical multi-detector array was created, arranging the trans-Stilbene modules in a regular tetrahedral configuration to optimize geometric efficiency. The detectors were evaluated under various operation modes (pulse height/charge) and tested for neutron/gamma discrimination using Pulse Shape Discrimination (PSD). Additionally, a multivariate approach employing Principal Component Analysis (PCA) was implemented to handle multiple pulse characteristic parameters effectively. The results highlight the potential of trans-Stilbene detectors to replace traditional C6D6 detectors at n_TOF/CERN, offering improved performance. The study also underscores their promising applications in both elastic and inelastic neutron scattering reactions, reinforcing their versatility and enhanced suitability for nuclear astrophysics research.